Phytobacter sp. RSE02 is a rice seed endophytic plant probiotic bacterium with human probiotic features and cholesterol-lowering ability - Santosh Kumar Jana; Rajarshi Bhattacharya; Sunanda Mukherjee; Samudra Gupta; Subhra Prakash Hui; Ansuman Chattopadhyay; Swadesh Ranjan Biswas; Sukhendu Mandal (Scientific Reports)
Abstract Research on seed microbiota has gained significant attention due to its role as a primary inoculum that enhances seedling growth, fitness, and productivity. This study explores the characteristics of the plant-probiotic seed-endophyte Phytobacter sp. RSE02, which demonstrates distinctive beneficial probiotic features in animal models. We examine the safety and probiotic potential of RSE02 in human cell lines, zebrafish, and mice. Notably, RSE02 can utilize cholesterol as its sole carbon source; however, it does not adhere to the Caco-2 cell line or the zebrafish gut. Importantly, RSE02 is non-toxic across all tested models. We further explore its cholesterol-utilizing ability to determine its efficacy in mitigating hypercholesterolemia and body fat deposits in mice when administered orally. In a high-fat diet mouse model, RSE02 significantly lowered blood cholesterol levels and reduced body weight, peritoneal fat deposits, and liver weight. Additionally, the treatment with RSE02 led to decreased levels of total blood protein, MDA, and GSH in high-fat diet mice. Genomic analysis of RSE02 revealed the absence of virulence or toxin-producing genes while identifying gene clusters responsible for synthesizing key vitamins such as folate, biotin, and vitamin B12. The findings highlight the dual functionality of Phytobacter sp. RSE02 in enhancing plant and animal health, challenging traditional notions of probiotics, and offering prospects for innovative solutions in sustainable agriculture and cardiovascular health interventions.